Health Awareness and Study Performance in Public Educational Type Sports Schools - Kalman, Klara (Central European Journal of Educational Research, 2021)
Book review on Kovács, K.E. (2020). Health and Learning in Public Educational Type Sports Schools. University of Debrecen: CHERD-Hungary. ISBN 978-615-6012-03-6